Study of correlation of presence of microalbuminuria to target organ damage in essential hypertension cases - Bhole, Pragati; Aher, Archana (International Journal of Advances in Medicine, 2018)
Background: Critical amount of urinary albumin excretion has long been reported to be one strong predictor of cardiovascular events in hypertensive patients. Very few studies have been conducted till now depicting correlation of microalbuminuria and target organ damage in patients with essential hypertension, except cardiovascular events. We evaluated the prevalence of microalbuminuria in patients with essential hypertension and its relationship with target organ damage. Methods: Total 120 patients of essential hypertension were studied. Prevalence of urinary albumin excretion and its correlation to target organ damage (left ventricular hypertrophy, retinopathy and stroke) was analysed. Urinary albumin excretion was assessed by turbidimetry method and microalbuminuria was assessed by urine albumin to creatinine ratio. Results: Microalbuminuria was found to be present in 57.7% patients. Target organ damage was observed in 62.5% (75) patients, out of which 78.66% patients had associated microalbuminuria (p <0.05). Amongst them, higher prevalence was observed in patients with longer duration and greater severity of hypertension, increased body mass index and dyslipidemia. Conclusions: Microalbuminuria assessment in hypertensive patients is an important test for the evaluation of target organ damage. Optimal management of hypertension, weight control, and maintenance of normal lipid levels leads to decreased risk of microalbuminuria.